2012
DOI: 10.1055/s-0039-1698926
|View full text |Cite
|
Sign up to set email alerts
|

Bonding of adhesives to Er:YAG laser-treated dentin

Abstract: Objective:The shear bond strength of adhesives applied to dentin was investigated after irradiation with an erbium-doped yttrium aluminum garnet (Er:YAG) laser.Methods:Superficial and deep dentin specimens from human molars were treated either with carbide bur or an Er:YAG laser. Two etch and rinse adhesives (Single Bond and XP Bond) and two self-etch adhesives (Prompt L-Pop and Xeno III) were employed to bond the composite. Shear bond strength (SBS) was determined after storage in water for 24 h using a unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 28 publications
4
14
0
1
Order By: Relevance
“…Bonding to permanent teeth has been studied extensively. The results of this study about the performance of Single Bond and Clearfil SE Bond were in accord with those by Celik et al 22 and da Silva et al 23 and in contrast to the studies by Ramos et al, 15 De Munck et al, 17 and Koliniotou-Koumpia et al 14 The results of the present study cannot be reliably compared to the outcomes of the conducted research on the permanent teeth. Many studies have suggested that the permanent tooth dentin has some morphological and structural differences in comparison with primary tooth dentin.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Bonding to permanent teeth has been studied extensively. The results of this study about the performance of Single Bond and Clearfil SE Bond were in accord with those by Celik et al 22 and da Silva et al 23 and in contrast to the studies by Ramos et al, 15 De Munck et al, 17 and Koliniotou-Koumpia et al 14 The results of the present study cannot be reliably compared to the outcomes of the conducted research on the permanent teeth. Many studies have suggested that the permanent tooth dentin has some morphological and structural differences in comparison with primary tooth dentin.…”
Section: Discussionsupporting
confidence: 88%
“…Some studies found laser treatment to negatively influence the bond strength and leakage of adhesive dentin interface. [14][15][16][17][18][19][20][21] Some other results have reported no difference in the bond strength or leakage of adhesive restorations between bur and laser prepared restorative cavities. [22][23][24][25] At different laser parameters, different amount of tooth ablation and thermo-chemical changes occur on tooth surfaces, resulting in different performances from the same adhesives.…”
Section: Introductionmentioning
confidence: 99%
“…This outcome is associated with the disintegration and structural changes in dentin tubules corresponding to the excessive energy. Ceballo et al [33] and Koliniotou-Koumpia et al [20] reported denaturing of the tooth surface collagen ber following laser irradiation. The denaturing of collagen bers reduces surface porosity, which is not conducive to the penetration of adhesive [34].…”
Section: Discussionmentioning
confidence: 99%
“…[16] Several studies have shown that the microleakage is minimal when the bonding between the restoration and the tooth is adequate. [12,18,27,30,[33][34][35][36] Several previous studies similar to ours investigated the effects of preparation with an erbium laser and convantional burs on marginal microleakage. [10,14,24,[37][38][39][40] Some of these studies found that lasers produced equal or better microleakage scores than burs, [38][39][40] and other studies have reported the opposite.…”
Section: P>005 For All Groupsmentioning
confidence: 99%